Reclassification of other comprehensive income, earnings management and earnings quality: evidence from Indonesia / Marhaendra Kusuma, Grahita Chandrarin and Diyah Sukanti Cahyaningsih - Kusuma, Marhaendra; Chandrarin, Grahita; Cahyaningsih, Diyah Sukanti (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2022)
This study empirically proves that standard policies concerning the format of presenting income statements are in the form of additional information. This is particularly relevant to the reclassification of other comprehensive income and profit attribution in increasing transparency and reducing asymmetry information. This study investigated the effect of reclassified items concerning other comprehensive income and net income attributable to owners on earnings management and the quality of earnings. The attribution of earnings to owners was found to have a negative effect on earnings management, along with a positive effect on earnings quality as measured by the earnings response coefficient net and comprehensive income. It was also shown that earnings management does not mediate the effect to earnings quality. Accordingly, this means that the market has responded positively to the reclassification of other comprehensive income and profit attribution. It also precludes the company from carrying out earnings management through the recognition and realisation of other comprehensive income. Reclassification and attribution through increasing transparency and value relevance could consequently reduce asymmetric information.